Identification and characterization of an imidazolium by‐product formed during the synthesis of 4‐methylmethcathinone (mephedrone). Issue 10 (1st April 2015) - Power, John D.; Kavanagh, Pierce; McLaughlin, Gavin; O'Brien, John; Talbot, Brian; Barry, Michael; Twamley, Brendan; Dowling, Geraldine; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> 4‐Methylmethcathinone (2‐methylamino‐1‐(4‐methylphenyl)propan‐1‐one, mephedrone) is a psychoactive substance that has been associated with recreational use worldwide. Analytical data related to mephedrone are abundantly available but the characterization of by‐products obtained during organic synthesis remains to be explored. This study presents the identification of a 1, 2, 3, 5‐tetramethyl‐4‐(4‐methylphenyl)‐1H‐imidazol‐3‐ium salt (TMMPI), which was formed during the synthesis of mephedrone. When diethyl ether was added to the crude reaction product, solid material precipitated from the solution. Analytical characterization of TMMPI employed a range of analytical techniques including chromatographic analysis in combination with various mass spectrometric detection methods, nuclear magnetic resonance spectroscopy, and crystal structure analysis. Additional confirmation was obtained from organic synthesis of the imidazolium by‐product. When TMMPI was subjected to analysis by gas chromatography–mass spectrometry (GC‐MS), isomerization and degradation into two distinct compounds were observed, which pointed towards thermal instability under GC conditions. A liquid chromatography‐mass spectrometry (LC‐MS) based investigation into a micro‐scale synthesis of mephedrone and three additional analogues revealed that the corresponding TMMPI analogue was formed. Interestingly, storage of mephedrone freebase in a number of organic solvents also gave rise to TMMPI and it appeared that its formation during storage was significantly reduced in the absence of air. The present study aimed to support clandestine forensic investigations by employing analytical strategies that are applicable to manufacturing sites. The imidazolium salts will most likely be found amongst the waste products of any clandestine lab site under investigation rather than with the desired product. Copyright © 2015 John Wiley & Sons, Ltd.